Implementasi RFID untuk Tracking Rute Perjalanan Kereta Api dan Penggerak Wesel Secara Otomatis - Erricson Bernedy Setiawan; Rakhmadhany Primananda; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
information regarding train travel routes has not been clearly recorded while at the station or leaving the station, this causes passengers to experience confusion to find that information. The application of RFID technology in every station that is passed by the train will get real-time and Web-based information. So that passengers feel more comfortable to have the history of train travel and the leadership of the station can calculate the time of arrival of each train are seen on the website. The RFID tags installed on the locomotive stores the information needed, which is the train ID, destination, previous station, current station, and next station. After identification, the information will be recorded automatically in a database, then the information on the RFID tag will be updated according to the next trip. The information is also used to move the Wessel automatically according to the destination to be addressed. This system applies a Wireless Sensor Node by using NRF24L01 as a communication module. The RFID-RC522 module was chosen because not only can it be used to identify RFID tags, but it can also perform writing modes to block data on the RFID Tag. The interface used consists of a desktop-based interface that is used when wanting to update information on RFID Tags and a web-based interface is used to display information about train travel history in real-time. There are two tests on this system, namely functional testing and performance testing. In functional testing, the base station can communicate with sensor nodes and actuators, sensor nodes can identify and update data on RFID tags, actuators work according to commands given by the base station, then the base station can perform automatic updates to the database. Performance testing is measured by sending delay parameters between nodes in each process. The results of testing when identifying an average delay of 63,875ms, when updating information received an average delay of 44,625ms, and testing on the branching path got an average delay of 21.5ms.